A New Record of Oxytricha granulifera granulifera Foissner and Adam, 1983 (Protozoa, Ciliophora, Oxytrichidae) From a Hot Spring in Iceland, With Notes on Its Abnormal Form During Cultivation - Zhu, Rong; Qu, Zhishuai; Zhang, Qi; Filker, Sabine; Stoeck, Thorsten; Li, Fengchao; Hu, Xiaozhong (Frontiers in Marine Science, 2021)
We isolated a population of Oxytricha granulifera granulifera Foissner & Adam, 1983 from a hot spring in Iceland. The pure culture of this isolate was established at room temperature in the laboratory. This allowed for a detailed investigation, informed by integrated approaches, of the isolate’s morphology and morphogenesis, as well as molecular phylogeny. Results showed that the morphological and morphogenetic characteristics of the Iceland population are consistent with those of other populations. During the three-year long period of laboratory cultivation, some abnormal individuals appeared repeatedly in the culture system. Interestingly, the morphological characteristics of these abnormal cells were rather stable, and were as follows: 1) body slender and elliptical-shaped; 2) remarkably shortened adoral zone and significantly reduced number of adoral membranelles; and 3) loss of undulating membranes. Resting cysts, binary fission and conjugate reproduction were not found in abnormal specimens. Although the morphology of abnormal individuals changed significantly, the sequences of the SSU rDNA of the normal and abnormal morphotypes were the same. Phylogenetic analyses showed that the two morphotypes clustered in a clade with other populations of O. granulifera granulifera.